Cyber attack detection in IOT-WSN devices with threat intelligence using hidden and connected layer based architectures - S. Nandhini; A. Rajeswari; N. R. Shanker (Journal of Cloud Computing: Advances, Systems and Applications)
Abstract In this paper, cyber-attacks in IOT-WSN are detected through proposed optimized-Neural Network algorithms such as (i) Equilibrium Optimizer Neural Network (EO-NN), (ii) Particle Swarm Optimization (PSO-NN), (iii) Single Candidate Optimizer Neural Network (SCO-NN) and (iv) Single Candidate Optimizer Long Short-Term Memory (SCO-LSTM) with different connecting, hidden neural network layers and threat intelligence data. The proposed algorithms detect the attacker node, which frequently changes the behaviour such as attacker node/ normal node. Existing IDS system detects the attacks in WSN and unable to detect the changing behavior attacker nodes in IOT-WSN. The behaviour of attacker node changes from normal behaviour to attacker behaviour due to nodes connected to internet continuously. The classification accuracy rates of proposed SCO-LSTM algorithm without and with threat intelligence are about 99.7% and 99.89%, respectively.